Dietary fiber: fractionation, characterization and potential sources from defatted oilseeds - Nevara, Gita Addelia; Syed Muhammad, Sharifah Kharidah; Zawawi, Norhasnida; Mustapha, Nor Afizah; Karim, Roselina (Multidisciplinary Digital Publishing Institute, 2021)
Dietary fiber (DF) has wide applications, especially in the food and pharmaceutical industries due to its health-promoting effects and potential techno-functional properties in developing functional food products. There is a growing interest in studies related to DF; nevertheless, there is less focus on the fractionation and characterization of DF. The characteristics of DF fractions explain their functionality in food products and provide clues to their physiological effects in food and pharmaceutical industrial applications. The review focuses on a brief introduction to DF and methods for its fractionation. It discusses the characterization of DF in terms of structural, physicochemical and rheological properties. The potential sources of DF from selected defatted oilseeds for future studies are highlighted.